Moral change and the purchase-sale relationship: Critical analysis of Swiss and German companies - Marco Schmaeh; Allessandro Siblio; Patrick Höra; Jessica Sager; Leon Winter; Benjamin Schwegler (The Institute of Academic Research and Publication (IARP), 2022)
This study examines the awareness and causes of moral change from the economic perspective in Germany and Switzerland. Based on an analysis of value research to date and interviews with experts in B2B sales, the manifestations of moral change are critically examined and recommendations for action are derived on an employee-specific and company-wide level.